اللغة العربية في سياق اللغات السامية - Bahauddin, Muhammad (UAS PRESS, 2018)
The birth of Arabic in the form of what is now started from a long civilization in the past. The scientists then classi????ied the language, including the language revealed by Noah›s children who later spread in various languages in the world, especially Arabic. Sam language became the language of his Arabic ancestors. But what is the difference between these languages and other European languages? This needs to be known so that the horizon related to the language is wide open.